Low-carbon concrete and preparation method thereof
By using alternative materials such as blast furnace slag, recycled clay brick powder and wood fiber in low-carbon concrete, combined with alkali exciter technology, the problem of low replacement rate of existing low-carbon concrete cement is solved, and the effect of efficiently reducing carbon emissions and improving concrete performance is achieved.
Patent Information
- Application Number
- CN202510124866.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-15
AI Technical Summary
In tunnel and underground projects, the cement replacement rate of existing low-carbon concrete is relatively low, which makes it difficult to effectively reduce carbon emissions.
By using alternative materials such as blast furnace slag, recycled clay brick powder and wood fiber, combined with alkali exciter technology, a low-carbon concrete formula is designed to reduce cement content and improve the strength and durability of concrete.
The cement substitution rate has been improved, carbon dioxide emissions have been reduced, up to 70%, and the fluidity and construction convenience of concrete are guaranteed.
Smart Images

Figure CN119822746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to low-carbon concrete and a preparation method thereof. Background Art
[0002] In the process of promoting modernization, we should adhere to high-quality development as the core, while actively practicing the concept of green development, promoting efficient use of resources, reducing environmental pollution, and laying a solid and green foundation for the comprehensive construction of a modern country.
[0003] As an indispensable part of the transportation system, tunnels play an important role in enhancing traffic safety and coping with special terrain. However, during the construction of tunnels, the average carbon emissions per kilometer of highway tunnels reach about 2,247 tons, the average carbon emissions per kilometer of railway tunnels reach about 2,556 tons, and the carbon emissions of open-cut cast-in-place subway stations even reach about 55,075 tons. According to the average carbon trading price of 68.15 yuan / t in my country in 2023, the carbon cost of tunnels and underground projects alone can reach millions of yuan. At the same time, relevant carbon emission assessment studies have shown that about 80% of carbon emissions come from the material production stage, among which concrete and steel bars account for the largest proportion of carbon emissions, which is mainly due to the largest use of both in tunnels and underground projects. It takes about 10,000 tons of concrete and 45 tons of steel bars to build 1 km of tunnel. Therefore, the use of high-strength steel bars and low-carbon concrete in tunnels and underground projects is one of the effective measures to reduce carbon emissions.
[0004] Blast furnace slag is currently a commonly used supplementary cementitious material for producing low-carbon concrete. In some existing studies, Huimin Pan et al. determined that the performance of the prepared low-carbon concrete was optimal when the water content was 35%, the cement content was 10%, and the ratio of steel slag: GGBS to fly ash: GGBS was 1:1, realizing the resource utilization of low-activity, highly doped steel slag. Bachene Sara et al. used fine particles of construction and demolition (C&D) waste as a substitute for natural sand and ground granulated blast furnace slag (GGBFS) as a substitute for cement. There are also studies on the use of silica fume (SF), fly ash (FA), slag powder (SP), waste glass powder (WGP), etc. to make low-carbon concrete. In addition, some scholars use recycled materials and industrial waste to work together to replace cement, thereby reducing carbon dioxide emissions. Gaofeng Chen et al. studied a new type of low-carbon concrete containing recycled clay brick powder (RCBP) and ground blast furnace slag (GGBFS), and the cement replacement rate can reach 20%. However, due to the volcanic ash reaction, the strength of concrete with a higher replacement rate will decrease. Current research suggests that it is more appropriate to control the amount of RCBP added to 5% to 15%, and the cement replacement rate is not high.
[0005] Therefore, how to design a concrete product with a high cement replacement rate, low carbon and environmental protection is an urgent problem to be solved by technical personnel in this field. Summary of the invention
[0006] One of the purposes of the present invention is to provide a low-carbon concrete in view of the deficiencies in the prior art, which can significantly reduce the cement content while meeting standard indicators, thereby achieving the purpose of reducing carbon emissions.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned low-carbon concrete, which has a simple and convenient preparation process and can meet the needs of on-site construction.
[0008] The technical solution to achieve one of the purposes of the present invention is: a low-carbon concrete comprising the following components:
[0009] Cement 1.6~16.1wt%
[0010] Brick powder 0~4.8wt%
[0011] Blast furnace slag 0~12.9wt%,
[0012] Coarse aggregate 35.1~55.1wt%,
[0013] Fine aggregate 17.4~37.4wt%,
[0014] Wood fiber 0~1.2wt%,
[0015] Water reducing agent 0~0.2wt%,
[0016] Water 9.8~10.6wt%
[0017] Alkali activator 0~0.9wt%.
[0018] Preferably, the following components are included:
[0019] Cement 3.2wt%,
[0020] Brick powder 3.2wt%,
[0021] Blast furnace slag 9.7wt%,
[0022] Coarse aggregate 45.1wt%,
[0023] Fine aggregate 27.4wt%,
[0024] Wood fiber 0.8wt%,
[0025] Water reducing agent 0.2wt%,
[0026] Water 9.8wt%,
[0027] Alkali activator 0.6wt%.
[0028] Furthermore, the brick powder is recycled clay brick powder, the glass phase content is 60wt%, the activity index is 73.6%, and the preparation method is:
[0029] Take building red bricks, wash, dry and crush them, first process them in a drum ball mill for 10 minutes, and then grind them in a planetary ball mill for 10 minutes.
[0030] Furthermore, the alkali activator is water glass, the modulus is 1.65, and the alkali content is 4wt%.
[0031] Furthermore, the coarse aggregate is basalt aggregate with a particle size of 5-10 mm.
[0032] Furthermore, the fine aggregate is natural river sand with an apparent density of 2.65 g / cm 3 , fineness modulus is 2.4.
[0033] Furthermore, the wood fiber is paper scraps or recycled paper scraps, the fineness is 1.5-2.5 dtex, and the water reducer is a polycarboxylic acid type water reducer.
[0034] The technical solution for achieving the second object of the present invention is: any method for preparing the above-mentioned low-carbon concrete comprises the following steps:
[0035] 1) Take materials in proportion;
[0036] 2) Add cement and brick powder into a stirrer and mix, take part of the water, add an alkali activator to prepare an alkali activator solution with an alkali content of 4wt%, mix the blast furnace slag and the alkali activator solution, soak and add to the stirrer;
[0037] 3) Continue to add water reducer and remaining water, stirring until it reaches a flowing consistency;
[0038] 4) Add coarse aggregate and fine aggregate and mix well;
[0039] 5) Add wood fiber, stir and mix well to obtain low-carbon concrete.
[0040] Furthermore, in step 2), the mixing time of cement and brick powder is 3 minutes, the mixing time of blast furnace slag and alkali activator solution is 2 minutes, the soaking time is 5 minutes, and the ratio of water taken in step 2) to water taken in step 3) is 5:5.6.
[0041] Furthermore, the stirring time in step 3) is 10 minutes, the mixing time in step 4) is 5 minutes, and the stirring speed in step 5) during the process of adding wood fiber is lower than the stirring speed after the addition is completed.
[0042] The above technical solution has the following beneficial effects:
[0043] 1. The low-carbon concrete of the present invention, wherein the brick powder added is used as a low-calcium aluminum silicate material, and its main components are SiO2 and Al2O3. When an alkali activator is used, the silicate molecules are released into the system and participate in the formation of hydrated sodium aluminate silicate gel (NaSH). This product has the advantage of high porosity. Due to its high MgO content, blast furnace slag forms hydrotalcite during the alkalization process, which enhances the early strength of low-carbon concrete. The addition of wood fiber increases the bonding effect between the hydration product and the aggregate, and because the wood fiber itself absorbs water, it will prolong the setting time of the concrete, allowing the alkali-activated substance to be more widely diffused. With the increase of the curing time, the Ca / Si ratio in the system gradually increases, and the CaSH increases. This product has the characteristics of low porosity, and acts together with NaSH to provide high-quality mechanical properties for the structure, making the structural network more stable, and further strengthening the late strength of the concrete.
[0044] 2. The preparation method of the present invention has high efficiency in resource utilization, uses recycled clay brick powder and abrasive blast furnace slag, and recycles solid waste, which not only reduces the exploitation of natural resources, but also reduces the pressure of solid waste on the environment, which is in line with the concept of resource recycling and sustainable development.
[0045] Alkali activators are environmentally friendly. Alkali activator solution is prepared by using water glass powder and NaOH in a specific proportion. By precisely controlling the mass ratio of Na2O to binder, it can effectively stimulate the activity of materials such as slag, reduce the use of traditional cement, and reduce the high carbon emissions caused by cement production, reflecting the characteristics of low carbon and environmental protection.
[0046] It has good working performance. Under the premise of ensuring the fluidity of concrete, it reduces the water consumption, thereby improving the strength and durability of concrete and other properties. At the same time, it makes the concrete reach a flowing consistency, which is convenient for construction operation and ensures construction quality.
[0047] Adding wood fiber can improve the toughness and crack resistance of concrete, enhance the stability and durability of the concrete structure, effectively resist the damage to concrete by external factors, and extend the service life of concrete.
[0048] The technical effects of the order in which materials are added are:
[0049] Pouring dry cement and recycled clay brick powder into the mixer first to mix them is conducive to the uniform distribution of the two, so that other materials added subsequently can fully contact and react with them, laying the foundation for the formation of a uniform cementitious system and ensuring the uniform and stable overall performance of the concrete.
[0050] Mix the prepared alkali activator solution with abrasive blast furnace slag and soak for five minutes, so that the alkali activator can fully penetrate into the slag particles, stimulate the activity of the slag to the greatest extent, give full play to its potential cementing properties, and improve the strength and durability of the concrete. After the gel mixture is formed, add the water reducer and the remaining water for stirring. The water reducer can effectively disperse the particles such as cement, improve the fluidity of the particles, and make the water more evenly distributed in the system, further promote the hydration reaction between the materials, and improve the working performance and strength of the concrete. After the cementitious material is fully stirred, add the coarse and fine aggregates, so that the aggregate surface can be evenly coated with a layer of cementitious material, ensuring good bonding between the aggregate and the cementitious material, thereby improving the overall strength and stability of the concrete. Slowly add wood fiber and speed up the stirring speed after adding, so that the wood fiber can reach the best dispersion state in the concrete, evenly distribute it inside the concrete, give full play to its strengthening and toughening role, improve the crack resistance and toughness of the concrete, and will not cause fiber agglomeration or uneven dispersion due to premature addition.
[0051] The applicant has verified through experiments that the low-carbon concrete of the present invention can reduce the carbon dioxide emission rate by up to 70%, and is an environmentally friendly concrete product.
[0052] Further description is given below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is the compressive strength diagram of each sample in Example 1;
[0054] Figure 2 is a graph showing the compressive strength ratio of each sample in Example 1 to ordinary silicate concrete;
[0055] Figure 3 It is the cost diagram of each sample in Example 2;
[0056] Figure 4 This is the carbon emission diagram of each sample in Example 3;
[0057] Figure 5 This is a diagram of the compressive strength, cost-effectiveness, and carbon emission evaluation factors of each sample in Example 4. DETAILED DESCRIPTION
[0058] In the present invention, the cement used is P·O 42.5 cement, the blast furnace slag adopts S95 ore powder produced by Henan Bangneng Metal Materials Co., Ltd., the alkali activator is water glass (modulus is 1.65, commercially available, Na2O·SiO2·9H2O), and NaOH is used for modulus adjustment. Clay brick powder is ordinary building discarded red bricks, the surface is cleaned by a high-pressure water gun, and then dried by a dryer, the waste clay bricks are crushed and sieved, and then these aggregates are first processed in a drum ball mill for 10 minutes, and then ground in a planetary ball mill for 10 minutes to obtain brick powder. Wood fiber was purchased from Zhejiang Baofeng Mineral Processing Plant, taken from waste recycled paper scraps, and the fineness was 2.02dtex. The water reducer is a liquid polycarboxylic acid type high-efficiency water reducer. Other materials are all commercially available.
[0059] Example 1
[0060] Make the proportions according to the following table:
[0061] Concrete mix ratio (wt%)
[0062]
[0063] Note: Brick powder (RCBP), blast furnace slag (GGBFS), wood fiber (WF), cement (Cerment).
[0064] All raw materials are uniformly mixed using a mixer at room temperature (24±2°C). Taking the preparation of standard mechanical specimens as an example, the alkali activator is prepared before the experiment. 5% of 30°C warm water is poured into a beaker, and then 0.6% of water glass powder and a certain amount of 1mol / LNaOH are poured into the water to ensure that the mass ratio of Na2O to the binder is 4%. Then the formal production of concrete begins, taking the example concrete as an example. First, 3.2% of dry cement and 3.2% of recycled clay brick powder are poured into a mixer to mix, and then the prepared alkali activator with an alkali content of 4% is mixed with 9.7% of abrasive blast furnace slag, soaked for five minutes to make it fully contact, and then the colloidal mixture is added to the mixer. After continuing to stir for 2 minutes, 0.2% of water reducer (PS) and the remaining 5.6% of water are added and stirred for 10 minutes until a flowing consistency is reached. Then 45.1% of coarse aggregate and 27.4% of fine aggregate were added to the mixer and mixed for 5 minutes. Finally, 0.8% of wood fiber (WF) was slowly mixed in. The addition process was slowly stirred continuously. After the addition was completed, the stirring speed was increased until the fiber reached the best dispersion state. The mixed slurry was then poured into a 50×50×50mm mold, demolded after a 3-day curing period, and tested at 7 and 28 days of curing.
[0065] The test was conducted with a concrete cube specimen of 400 mm in size and a 300KN electro-hydraulic servo-controlled compression device at a speed of 1KN / s. The curing ages of the test specimens were 7 and 28 days respectively.
[0066] The compressive strength test was used to characterize the changes in the strength of different concretes, and the results are as follows: Figure 1 and Figure 2 are the compressive strength of each concrete and the compressive strength ratio of each concrete to ordinary silicate concrete. Figure 1 As shown in the figure, with the increase of curing age, the compressive strength of each test sample gradually increases. The strength of concrete with 80% abrasive blast furnace slag alone is not as high as that of concrete with 20% brick powder and 60% abrasive blast furnace slag. The addition of wood fiber (WF) will increase the later strength of concrete with the same brick powder content, but there is a trend of reducing the early strength. Compared with R20-G60-1, when the mass ratio of WF to brick powder reaches 1 / 4, the early strength and later strength increase by 5% to 15%. Keeping this mass ratio, as the amount of brick powder replacement increases, the strength of the sample develops inversely proportional to it. Brick powder only plays a filling role in the early stage, so as the proportion of cement replaced by it increases, the strength of concrete decreases. At room temperature, the active SiO2 and Al2O3 in the brick powder added early react with CH and water to form silicate hydrates. As the curing age increases, the pozzolanic activity of the brick powder gradually takes effect. The addition of WF enhances the bonding effect between the hydration products and aggregates, further strengthening the later strength of the concrete.
[0067] Example 2 Cost-Benefit Analysis
[0068] Cost analysis mainly considers raw material prices and transportation costs. According to the data released by the Chongqing Price Bureau in 2024, the price of cement is 460 yuan / ton. In the same year, the prices of standard sand and gravel, blast furnace slag, water, and waste paperboard are 240 yuan / t, 100 yuan / t, and 3.5 yuan / t, respectively. As mentioned above, brick powder is obtained from waste, and the price is tentatively set at 0 in this article. The transportation cost of using a 10-ton gasoline truck and a diesel truck is set at 0.6 yuan / (t·km). The transportation distance is set to 30km.
[0069] The raw material price can be calculated as:
[0070]
[0071] Shipping costs can be calculated as:
[0072]
[0073] Where C R is the total cost of raw materials, M i is the consumption of the i-th material, Ri is the unit price of the i-th material, C Y is the transportation cost of raw materials, D i The unit price is per unit weight and transportation distance.
[0074] Figure 3 The cost of each experimental group set up by the present invention is shown. In terms of total cost, silicate cement costs the most, and R30-G60 costs the least. It can be seen that the cost of aggregate is the highest, accounting for 27.8% of the cost of silicate cement, and the cost of cementitious materials in the remaining groups is lower than the cost of transportation. When the cement replacement rate is 80%, the cost of production using different low-carbon materials is 18% to 20% lower than that of silicate cement. When the replacement rate reaches 90%, the cost can be reduced by 23%. However, the overall benefit of using RCBP and other materials as partial substitutes for cement to prepare concrete should not only focus on the cost savings itself, but should also consider the changes in concrete strength and other properties to evaluate.
[0075] Example 3 Carbon dioxide emission analysis
[0076] Carbon dioxide emissions are calculated according to the current national standards "Principles and Framework for Environmental Management Life Cycle Assessment" GB / T 24040 and "Requirements and Guidelines for Environmental Management Life Cycle Assessment" GB / T 24044.
[0077] Emissions from each type of concrete during production can be calculated as:
[0078]
[0079] Among them C F is the CO2 emission of concrete, CO 2i is the CO2 emission per unit mass of concrete ingredients (carbon emission factors, as shown in Table 3). Sustainable concrete contains water, cement, slag, recycled clay brick powder, wood fiber, fine aggregate, coarse aggregate and a water reducer (polycarboxylate water reducer).
[0080]
[0081]
[0082] Figure 4 The carbon emissions per cubic meter of concrete produced by each experimental group are shown. As can be seen from the figure, carbon dioxide emissions mainly come from the use of Portland cement. The use of low-carbon materials such as slag, RCBP and WF can effectively reduce carbon dioxide emissions. In this study, the use of pure Portland cement to produce each cubic meter of concrete emits up to 303.56 kg of CO2. The experimental group set two cement replacement rates of 80% and 90%, and the efficiency of reducing carbon dioxide was 72% and 80% respectively.
[0083] Example 4 Feasibility Analysis
[0084] In order to investigate the specific feasibility of the test group, three factors, namely, compressive strength (Example 1), cost-effectiveness (Example 2) and carbon emissions (Example 3), were selected for comprehensive consideration. The changes in influencing factors of different test groups were calculated with OPC as a reference to obtain a low-carbon concrete mix ratio that meets both strength requirements and environmental benefits.
[0085] like Figure 5 As shown, the change in compressive strength has a negative effect on the system and a negative value is used, while the use of low-carbon materials to achieve cost savings and reduce carbon dioxide emissions are both positive and positive. Finally, the system is evaluated as a whole. It can be seen from the figure that R20-G60-3 has the best overall index, followed by R30-G60. The index of only adding GGBFS is the smallest, and the remaining groups are 30% different from the optimal solution. The results are similar to the previous mechanical properties and microscopic analysis results, which can verify each other.
Claims
1. A low-carbon concrete, characterized in that: Includes the following components: Cement 1.6~16.1wt% Brick powder 0~4.8wt% Blast furnace slag 0~12.9wt%, Coarse aggregate 35.1~55.1wt%, Fine aggregate 17.4~37.4wt%, Wood fiber 0~1.2wt%, Water reducing agent 0~0.2wt%, Water 9.8~10.6wt% Alkali activator 0~0.9wt%.
2. The low carbon concrete according to claim 1, characterized in that: The components include: Cement 3.2wt%, Brick powder 3.2wt%, Blast furnace slag 9.7wt%, Coarse aggregate 45.1wt%, Fine aggregate 27.4wt%, Wood fiber 0.8wt%, Water reducing agent 0.2wt%, Water 9.8wt%, Alkali activator 0.6wt%.
3. The low carbon concrete according to claim 1 or 2, characterized in that: The brick powder is recycled clay brick powder, the glass phase content is 60wt%, the activity index is 73.6%, and the preparation method is: Take the building red bricks, wash, dry, and crush them. First, process them in a drum ball mill for 10 minutes, and then grind them in a planetary ball mill for 10 minutes.
4. The low carbon concrete according to claim 1 or 2, characterized in that: The alkali activator is water glass, the modulus is 1.65, and the alkali content is 4wt%.
5. The low carbon concrete according to claim 1 or 2, characterized in that: The coarse aggregate is basalt aggregate with a particle size of 5-10 mm.
6. The low carbon concrete according to claim 1 or 2, characterized in that: The fine aggregate is natural river sand with an apparent density of 2.65 g / cm 3 , fineness modulus is 2.
4.
7. The low carbon concrete according to claim 1 or 2, characterized in that: The wood fiber is paper scraps or recycled paper scraps with a fineness of 1.5-2.5 dtex, and the water reducer is a polycarboxylic acid type water reducer.
8. The method for preparing low-carbon concrete according to any one of claims 1 to 7, characterized in that: The steps include: 1) Take materials in proportion; 2) Add cement and brick powder into a stirrer and mix, take part of the water, add an alkali activator to prepare an alkali activator solution with an alkali content of 4wt%, mix the blast furnace slag and the alkali activator solution, soak and add to the stirrer; 3) Continue to add water reducer and remaining water, stirring until it reaches a flowing consistency; 4) Add coarse aggregate and fine aggregate and mix well; 5) Add wood fiber, stir and mix well to obtain low-carbon concrete.
9. The preparation method according to claim 8, characterized in that: The mixing time of cement and brick powder in step 2) is 3 minutes, the mixing time of blast furnace slag and alkali activator solution is 2 minutes, the soaking time is 5 minutes, and the ratio of water taken in step 2) to water taken in step 3) is 5:5.
6.
10. The preparation method according to claim 8, characterized in that: The stirring time of step 3) is 10 minutes, the mixing time of step 4) is 5 minutes, and the stirring speed of step 5) during the process of adding wood fiber is lower than the stirring speed after the addition is completed.
Citation Information
Patent Citations
Wood fiber self-compacting concrete
CN112194418A